Pengaruh Fraksi Volume Serat Pada Green Composite Serat Bambu Dengan Matriks Sari Pati Kentang Terhadap Kekuatan Impak Dan Water Absorption - Marpaung, Fery Sehat Wiguna; Kencanawati, Cok Istri Putri Kusuma; Astawa, Ketut (Teknik Desain Mekanika; Vol 13 No 2 (2024): April 2024 : Teknik Desain Mekanik, 2024)
Abstract Environmentally friendly composite materials are developed to meet human needs, such as in the automotive, aviation, and construction industries. The development of composite materials leads to the use of biodegradable materials, such as bamboo fiber, which is an environmentally friendly material. The composition of bamboo fiber has the potential to be used as a composite material. The advantages of using composites include lightweight material, corrosion resistance, and no machining process. Composites reinforced with natural fibers have a strength 40% stronger and lighter than glass fiber composites. Therefore, natural fiber composite materials can be projected to be an alternative material to replace synthetic fiber composites. Research was conducted on composites with a matrix of potato starch reinforced with bamboo fiber. The variation in the composition of the composite with the ratio (fiber: matrix) is 5%: 95%, 7.5%: 92.5%, and 10%: 90%. Mechanical testing and physical testing conducted on composite specimens are impact tests and water absorption tests. Specimen manufacture refers to ASTM D6110 and ASTM D570-98 standards. The research results obtained the highest water absorption at the fiber volume fraction: matrix of 90%:10% with an average water absorption value of 83.66% and the highest impact toughness value in composites with a fiber volume fraction ratio: matrix of 5%:95%, with an average impact toughness value of 0.059 J/mm2. These results are strengthened by observations of the impact test fracture cross-section, where the number of fibers is dominant compared to other variations and quite dominant fibers in the break condition (fiber break). Keywords: Green Composite, Impact Test, Water Absorption Test, Bamboo Fiber, Potato Starch..